Chewing behaviour and particle size distribution in faeces in sheep fed silages of whole-crop barley and grass - Hedlund, Susanna (SLU/Dept. of Animal Environment and Health (until 231231), 2017)
Sheep in Sweden are generally kept on pasture when suitable and fed with a diet consisting mainly of forage, composed mainly by grass, when kept indoors. Lamb production in Sweden is steadily growing and with that the interest of different feedstuff to get a profitable production. Whole-crop barley silage has a high content of nutrients and a higher digestibility in comparison to whole-crop spring-sown wheat and oat. The aim of this experiment was to study the effect of whole crop barley silage and grass silage harvested at different maturity stages on consumption, chewing behaviour and faecal particle size in sheep. The silages used were two grass silages harvested May 31 and June 30 and two whole-crop barley silages harvested at heading stage June 30 and at milk stage July 18. Eight wethers were divided into two 4 x 4 Latin Squares (four wethers and four periods) with one group fed forage only and the other group fed forage an rapeseed meal as protein supplementation. Each period was four weeks where the wethers were fed ad libitum during the first three weeks and during the fourth week they were fed restricted with 80% of ad libitum. At the end of the trial, all wethers had been fed all diets. During the restricted period they were kept in metabolic cages where all faeces were collected and their chewing patterns were registered. The live weight of the wethers, the body condition score and the feed intake was continuously measured throughout the trial. Samples of feed and faeces were collected daily during the restricted period. The dry matter intake as percentage of live weight was lower for grass silages compared to the barley silages (P < 0.01). No difference between the maturity stages was found regarding dry matter intake. The intake of neutral detergent fibre increased with advancing maturity of the grass silages, but this could not be seen for the whole-crop barley silages (P < 0.001). Time spent chewing ranged from 629 to709 minutes per day, time spent ruminating ranged from 475 to 542 minutes per day and time spent eating ranged from 141 to 175 minutes per day. This is in line with other studies. The particle size in faeces was effected by forage type (P < 0.05). The proportion of large particles was higher in wethers fed whole-crop barley silage harvested at milk stage compared to the other silages (P < 0.05). In conclusion, no large differences between the four treatments were found suggesting that whole-crop barley silages could be a suitable equivalent to grass silage in lamb production given that it is not harvested too late.